Proverbs in Translation: A Study Based on Some Identified Proverbs - Gayathree, S. (National Centre for Advanced Studies in Humanities and Social Sciences, 2017)
Translation is indispensable towards the march of globalization. It is an art of reproducing the substance of the original in target language(s); first in terms of meaning then in terms of style. In a way translation is the replacement of textual material in one language by equivalent textual material in other language(s). Many aspects ought to be taken into consideration with keen attention in the process of translation. The original should be viewed from word-level to pragmatic-level. Finding an appropriate equivalent or substituting with an apt parallel is the first and foremost process. Translation involves the studying of the Lexicon, grammatical structure and cultural context of the source language text, analyzing it in order to determine its meaning and then reconstructing the very substance to suit the structure and cultural context of the target language without any shortcomings. Finding the apt equivalence is the most important procedure in translation. In order to do a translation a translator should be familiar with the cultural aspects of the source language as well as the target language. A language has strong influence on the traditions, norms and culture of the people who speak the language. As far as proverbs, idiomatic phrases and such cultural aspects are concerned they ought to be substituted with parallels.